1997
DOI: 10.1542/peds.99.3.e9
|View full text |Cite
|
Sign up to set email alerts
|

PICNIC (Pediatric Investigators Collaborative Network on Infections in Canada) Study of the Role of Age and Respiratory Syncytial Virus Neutralizing Antibody on Respiratory Syncytial Virus Illness in Patients With Underlying Heart or Lung Disease

Abstract: ABSTRACT. Objective. To determine the effects of age and respiratory syncytial virus (RSV) antibody status on frequency and severity of RSV infections in children with underlying heart or lung disease.Design. Cohort study conducted during two consecutive RSV seasons.Setting. Ambulatory patients at eight Canadian pediatric tertiary care centers.Methods. Subjects under 3 years old with underlying heart disease who were digoxin-dependent or had not received corrective cardiac surgery or with underlying lung disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 12 publications
(12 reference statements)
0
17
0
5
Order By: Relevance
“…Several studies reported a higher RSVH rate in infants aged <12 months [29, 30, 36, 38]. In a retrospective study by Boyce et al [29], the estimated number of hospitalizations per 1000 children with CHD aged 6 to <12 months and 12 to <24 months were 63.5 and 18.2, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported a higher RSVH rate in infants aged <12 months [29, 30, 36, 38]. In a retrospective study by Boyce et al [29], the estimated number of hospitalizations per 1000 children with CHD aged 6 to <12 months and 12 to <24 months were 63.5 and 18.2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The relative risk in comparison with non-CHD patients was 1.4 (0.6–3.1), 1.6 (0.8–3.2), 2.7 (0.7–9.7), and 1.8 (1.0-3.3), respectively [30]. A significant decrease in frequency of RSV LRTI and RSVH was also observed with increasing age in the Canadian PICNIC study [36]. The RSVH rates in children with CHD aged 0–3, 3–6, 6–12 and 12–24 months were 360, 60, 0 and 10 per 1000, respectively [36].…”
Section: Resultsmentioning
confidence: 99%
“…The infants most at risk of severe disease are those under 6 weeks of age, those with bronchopulmonary dysplasia, congenital heart disease, or immunodeficiency, and those born prematurely. Hospital admission rates for these groups range between 5% and 30% (20,25). The mortality rate among children admitted to hospital is approximately 3% for those with heart and lung problems and up to 1% for those without these risk factors (11,25).…”
mentioning
confidence: 99%
“…Hospital admission rates for these groups range between 5% and 30% (20,25). The mortality rate among children admitted to hospital is approximately 3% for those with heart and lung problems and up to 1% for those without these risk factors (11,25). In adults and the elderly, RSV pneumonia is increasingly recognized as a significant cause of morbidity and mortality, being associated with more than 17,000 deaths annually between 1991 and 1998 (9, 22).…”
mentioning
confidence: 99%
“…Furthermore, more than half of RSV-hospitalized infants and a large percentage of infants who require mechanical ventilation and even die from RSV infection are previously healthy (3,5). These striking disease severity differences cannot be explained by existing neutralizing antibody titers alone (6) and are likely due to a combination of host factors and viral factors. Although this finding is not universally confirmed (7), RSV subgroup A has been shown in several studies to produce more severe disease than RSV-B (8 -12).…”
mentioning
confidence: 99%